A model to simulate the moment–rotation and crack width of FRC members reinforced with longitudinal bars. (1st October 2015) - Barros, Joaquim A.O.; Taheri, Mahsa; Salehian, Hamidreza
Highlights: Innovative model to determine the moment–rotation relationship of R/FRC elements. A stress–crack width relationship is used to model the post-cracking behavior of a FRC. A shear friction model is proposed for modeling the FRC compression softening. A model is adopted to simulate the bond between longitudinal bars and surrounding FRC. The good predictive performance is demonstrated by using available experimental data. Abstract: The present work describes a model for the determination of the moment–rotation relationship of a cross section of fiber reinforced concrete (FRC) elements that also include longitudinal bars for the flexural reinforcement (R/FRC). Since a stress–crack width relationship ( σ – w ) is used to model the post-cracking behavior of a FRC, the σ – w directly obtained from tensile tests, or derived from inverse analysis applied to the results obtained in three-point notched beam bending tests, can be adopted in this approach. For a more realistic assessment of the crack opening, a bond stress versus slip relationship is assumed to simulate the bond between longitudinal bars and surrounding FRC. To simulate the compression behavior of the FRC, a shear friction model is adopted based on the physical interpretation of the post-peak compression softening behavior registered in experimental tests. By allowing the formation of a compressive FRC wedge delimited by shear band zones, the concept of concrete crushing failure mode in beams failing in bending is reinterpreted. By using the moment–rotation relationship, an algorithm was developed to determine the force–deflection response of statically determinate R/FRC elements. The model is described in detail and its good predictive performance is demonstrated by using available experimental data. Parametric studies were executed to evidence the influence of relevant parameters of the model on the serviceability and ultimate design conditions of R/FRC elements failing in bending.